Predictors of Clinical Outcomes of Flexible Ureterorenoscopy with Holmium Laser for Renal Stone Greater than 2 cm - Saeed M. Al-Qahtani; Sixtina Gil-deiz-de-Medina; Olivier Traxer (Advances in Urology)
Objective. To evaluate the clinical outcome of flexible ureterorenoscopy (F-URS) with holmium laser in managing renal stone greater than 2 cm. Patients and Methods. Records of 120 patients (123 renal units) with renal stone greater than 2 cm who underwent F-URS with holmium laser iwere evaluated. The mean stone size was 26.3 mm. Patient and stone characteristics, perioperative outcomes and complications were evaluated. The outcome was determined at 4 weeks on plain radiograph (KUB) and Non-contrast CT scan (NCCT). Follow-up visit was up to 6 months to evaluate the clinical outcome and patients symptoms. Results. Stone burden was an independent predictor of FURS results. After first session of treatment, success rate was obtained in 72 renal units (58.5%). On the other hand, significant residual fragment was encountered in 51 renal units (41.5%). This was improved with “staged-therapy” to 87% and 96.7% after second and third session of treatment, respectively. Complications were recorded. They were managed in proper manner accordingly. Conclusion. This is an attractive, safe and effective technique. It is an ideal option for low volume complex stone with average burdens of 2 to 3 cm. Patient should be informed and consented about staged-therapy.